Retailing On Internet: A Study Of The Factors That Influence The Customer’s Buying Intention Among Students In A Public Institution Of Higher Learning - No Family Name - Hasan, Yulihasri (2004)
On-line commerce through Internet is obtaining attention from students today. Shift from physical store (brick and mortar) towards electronic store may be seen as continued innovation brought by home shopping method such as: catalog, TV and direct mail.